Recent pegmatite-hosted spodumene discoveries in Western Australia: insights for lithium exploration in Australia and globally. Issue 2 (3rd April 2022) - Phelps-Barber, Zoe; Trench, Allan; Groves, David I.
ABSTRACT: The discovery and development of world-class Lithium–Caesium–Tantalum (LCT) spodumene-bearing pegmatites in Western Australia underpins growth of a significant new sector of its mining industry. Recently, several new spodumene discoveries have been delineated in the Yilgarn and Pilbara Cratons. Contrary to exploration narratives that new economic mineral discoveries will generally be made at increasingly greater depths, beneath barren cover rocks, or in remote geological environments, all new lithium discoveries have clear surface expressions in relatively 'mature' greenstone belts. The exploration implication is that the search space for pegmatite-hosted spodumene deposits in Western Australia remains immature. These recently discovered LCT pegmatites have geological features relevant to exploration including their age, amphibolite-facies metamorphic setting and syn-metamorphic timing, and 3D geometry, particularly their typically gentle dips, that match other such world-class pegmatites globally. Further spodumene discoveries within pegmatites at or near surface are likely in the Archean terranes of Western Australia based on these consistent exploration criteria and supportive capital market conditions.